Identification of 55, 000 Replicated DNA Methylation QTL. Issue 1 (December 2018) - McRae, Allan; Marioni, Riccardo; Shah, Sonia; Yang, Jian; Powell, Joseph; Harris, Sarah; Gibson, Jude; Henders, Anjali; Bowdler, Lisa; Painter, Jodie; Murphy, Lee; Martin, Nicholas; et al.
Abstract DNA methylation plays an important role in the regulation of transcription. Genetic control of DNA methylation is a potential candidate for explaining the many identified SNP associations with disease that are not found in coding regions. We replicated 52, 916cis and 2, 025trans DNA methylation quantitative trait loci (mQTL) using methylation from whole blood measured on Illumina HumanMethylation450 arrays in the Brisbane Systems Genetics Study (n = 614 from 177 families) and the Lothian Birth Cohorts of 1921 and 1936 (combined n = 1366). Thetrans mQTL SNPs were found to be over-represented in 1 Mbp subtelomeric regions, and on chromosomes 16 and 19. There was a significant increase intrans mQTL DNA methylation sites in upstream and 5′ UTR regions. The genetic heritability of a number of complex traits and diseases was partitioned into components due to mQTL and the remainder of the genome. Significant enrichment was observed for height (p = 2.1 × 10−10 ), ulcerative colitis (p = 2 × 10−5 ), Crohn's disease (p = 6 × 10−8 ) and coronary artery disease (p = 5.5 × 10−6 ) when compared to a random sample of SNPs with matched minor allele frequency, although this enrichment is explained by the genomic location of the mQTL SNPs.